Preparation and Physical Properties of Segmented Thermoelectric YBa2Cu3O7-x-Ca3Co4O9Ceramics - P. Wannasut (2018)
© Published under licence by IOP Publishing Ltd. Segmented thermoelectric ceramics are now well known for their high conversion efficiency and are currently being investigated in both basic and applied energy researches. In this work, the successful preparation of the segmented thermoelectric YBa2Cu3O7-x-Ca3Co4O9(YBCO-CCO) ceramic by hot pressing method and the study on its physical properties were presented. Under the optimum hot pressing condition of 800 °C temperature, 1-hour holding time and 1-ton weight, the segmented YBCO-CCO sample showed two strongly connected layers with the relative density of about 96%. The X-ray diffraction (XRD) patterns indicated that each segment showed pure phase corresponding to each respective composition. Scanning electron microscopy (SEM) results confirmed the sharp interface and good adhesion between YBCO and CCO layers. Although the chemical analysis indicated the limited inter-layer diffusion near the interface, some elemental diffusion at the boundary was expected to be the source of this strong bonding.